Investigation and improvement of maintenance storage location by using simulation method / Fahzol Shawal Ahmad Shapiai - Ahmad Shapiai, Fahzol Shawal (2009)
The purpose of this project is to relocate the Recoiling Line maintenance storage to more strategic location. Factors affecting the relocation decision such as safety, movement of maintenance crew and space reduction has been discussed. One of the consideration is the storage location should be located at the safe area which is far from the crane movement and high voltage area. It is also considered the maintenance crew movement in term of dispatching the tools or spare parts in order to reduce their time during maintenance job. The new maintenance storage location will be compared to the new storage layout location by using CATIA software which involved the time, cost, space and safety. Then, the result will be analyzed and some recommendation will be proposed to the company in order to get the best location for the new storage area.